Influência da depleção no sistema maciço rochoso – pasta de cimento – revestimento em poços de petróleo - Dantas, José Diego Formiga (2015)
Pressure drawdown in oil producing fields can lead to reservoir compaction, surface subsidence and cementation/casing failure. The study and understanding of these effects can imply financial and environmental risks reduction. In order to analyze and predict these problems some models were built using the finite element software ABAQUS due to its flexibility in treatment of geometry and topological heterogeneity, use of external routines and plugins. This study describes, through axisymmetric models, the influence of 'depletion' and "coefficient of friction" on reservoir compaction, surface subsidence, von Mises stresses in the casing and slip between cement/casing was analyzed. A central composite rotatable design (CCRD) 22 with four axial points and a center point was made to analyze the significance of the variables through the response surface method. In addition to the quantitative variables, as indicated, it was also analyzed the influence of qualitative variable type of reservoir rock. It was concluded that depletion is a significant variable for the answers "Mises stress", "reservoir compaction" and "subsidence" while the variable coefficient of friction is significant for the answers "Mises stress" and "slip." The type of reservoir rock influences directly the Mises stress, compaction and subsidence. For the same depletion more rigid is the rock, less is the von Mises stress, compaction and subsidence. Also to realize a reduction in the maximum active tension in the coating, for the same level of depletion, friction coefficient and type of reservoir rock when concentric coatings run, due to increased structural capacity. Also was realize, for the same level of depletion, friction coefficient and type of reservoir rock, a reduction in the maximum active stress in the casing, when was used concentric casings, due to increased structural capacity.